2006
DOI: 10.1055/s-2006-926877
|View full text |Cite
|
Sign up to set email alerts
|

Lokale Nachexzision nach endoskopischer R1/R2-Polypektomie von pT1-„low-risk”- Karzinomen des Rektums durch transanale endoskopische Mikrochirurgie (TEM)

Abstract: The transanal endoscopic microsurgery (TEM) is an adequate method for the local full-thickness excision of large rectum polyps and pT1 "low-risk" rectal carcinomas. We studied prospectively the relevance of this surgical technique concerning complete tumour excision after R1/R2-polypectomy of malignant rectal polyps. 16 patients with pT1 "low-risk" rectal carcinoma and macroscopic (R2) or microscopic (R1) incomplete endoscopic polypectomy were locally resected by TEM. In 12 patients (75 %) no residual tumour w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…Overall, TES serves as a valuable diagnostic tool following incomplete polypectomy of unsuspected malignant pT1 polyps. Across various studies, TEM is reported to identify residual adenomatous and/or adenocarcinoma in up to 14.8 to 70% 20 21 22 23 of cases. When full-thickness TEM excision is performed for a residual pT1 tumor deemed low risk for nodal metastasis based on histologic review and/or staging with endoscopic ultrasound and/or pelvic MRI, TEM achieves good local control with acceptable local recurrence rates (see later section).…”
Section: Local Excision Of Early Rectal Cancer: Techniques Selection ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, TES serves as a valuable diagnostic tool following incomplete polypectomy of unsuspected malignant pT1 polyps. Across various studies, TEM is reported to identify residual adenomatous and/or adenocarcinoma in up to 14.8 to 70% 20 21 22 23 of cases. When full-thickness TEM excision is performed for a residual pT1 tumor deemed low risk for nodal metastasis based on histologic review and/or staging with endoscopic ultrasound and/or pelvic MRI, TEM achieves good local control with acceptable local recurrence rates (see later section).…”
Section: Local Excision Of Early Rectal Cancer: Techniques Selection ...mentioning
confidence: 99%
“…In such event, additional attempt at curative local excision using full-thickness TAE or TES may be considered, if no high-risk histopathological features are identified that warrant an oncologic resection. 20 21 22 23 However, if ESD was performed for an unsuspected malignant polyp, R0 resection might have been achieved if the focus of invasion was limited to the upper submucosal layer. If pathology review of the specimen determines that deep and lateral margins are conclusively negative, and if no adverse risk factors are identified to indicate a high risk of lymph node metastasis, ESD can, in some cases, achieve curative resection of superficial T1 rectal tumors.…”
Section: Local Excision Of Early Rectal Cancer: Techniques Selection ...mentioning
confidence: 99%
“…Bei R1-Resektion, unklaren Resektionsgrenzen (Rx), einem Resektionsrand <1 mm oder High-risk-Histologie war die Lokalrezidivrate signifikant höher (39%) als bei adäquater Resektion und Low-risk-Konstellation (6%). Dementsprechend sollte bei R1-Histologie oder ungenügendem Resektionsabstand eine radikale Nachresektion erfolgen [37].…”
Section: Lokale Chirurgische Resektionenunclassified
“…Transanal endoscopic microsurgery (TEM), which was invented by Dr. Buess in 1983, was put into constant use for the treatment of rectal carcinoma over years of practice [8][9][10]. The full-thickness resection makes it an advisable approach for low-risk early rectal cancer, according to several guidelines [9,[11][12][13][14]. Despite of the advantages, the de ciency of resecting lymph nodes in TEM resection remains highly controversial.…”
Section: Introductionmentioning
confidence: 99%